Optimasi Penugasan Menggunakan Metode Hungarian: Pada CV. L&J Express - Harini, Dwi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2017)
Assignment problems are a special form of linear programming problems that often occur in a company in allocating or placing a workforce that suits its ability. To solve the issue of assignment is to use Hungarian method. In applying the Hungarian method, the amount of labor assigned should be equal to the amount of work to be completed. The author uses Hungarian method to calculate the total delivery time of goods on CV. L & J Express Malang *) so as to get the optimal total delivery time. To solve the assignment problem on CV. L & J Express Malang, the required data includes employee name, destination location, and delivery time. Based on result of calculation using Hungarian method, obtained total delivery time of optimal goods equal to 105 minutes. Before using the Hungarian method the total delivery time of goods amounted to 119 minutes. It can be seen that there is a time efficiency of 14 minutes.